Skin and soft tissue infections caused by nontuberculous mycobacteria: A review of literature - Rutnin, Suthinee (Thai Journal of Dermatology, 2015)
Skin and soft tissue infections (SSTIs) caused by nontuberculous mycobacteria (NTM) are underrecognized and difficult to treat. Diagnosis can be challenging due to a variety of clinical presentations, low yield from cultured specimens, and nonspecific histopathology from skin biopsy. In addition, optimal medical and surgical management are controversial. This review focuses on updates in diagnostic tests along with clinical manifestation and management of NTM infections of skin and soft tissue.